PROBLEMS OF DETERMINING THE NEED FOR SPARE PARTS AND MATERIALS FOR THE MAINTENANCE OF AIRPORT SPECIAL EQUIPMENT - Tamargazin , Oleksandr; Pryimak, Liudmyla (Science-based technologies, 2024)
The modern conditions of airport operation are considered from the point of view of reducing tariffs for services by reducing the costs of special equipment operation. The main attention is paid to the analysis of the influence of the costs of spare parts and materials used in its maintenance on the cost of special equipment use. The processes of special equipment utilization at the airport are considered as stochastic, and the logistics system at the airport is considered as a mass service system. It is taken into account that the stochasticity of the system is conditioned not only by the properties of the processes, but also by the randomness of the factors influencing them. In this regard, to manage the system under consideration, the list of factors that determine the intensity of resource consumption, as well as the regularities of their changes is analyzed. The main attention is paid to the necessity to find a compromise between uninterrupted supply, which requires an increase in the size of orders, and the reduction in the volume of stocks, which increases the cost of working capital of the aviation enterprise. The influence of climatic conditions of operation on the consumption of resources for the maintenance of special equipment at the airport is also analyzed. The analysis has shown that the determination of the need for resources for the maintenance of special equipment at airports is currently planned on the basis of the actual consumption for the previous year and it is not practically taken into account that the consumption varies seasonally. In this regard, it is noted that the relevance of research aimed at developing methods for planning the need of special transport services of modern airports in spare parts and consumables for maintenance, taking into account the variation in the intensity and operating conditions of special equipment. The analyzed approaches to the development of such methods show the need to consider the process of determining the need for spare parts and consumables for maintenance of special equipment as non-stationary, due to seasonal changes in the intensity and operating conditions. On this basis the basic principles of development of theoretical provisions and practical recommendations for determining the size of stocks of spare parts and consumables for maintenance of special equipment are proposed.